Observations of the selected astronomical objects usingPolarization-Holographic Imaging Stokes Polarimeter - Kurkhuli, G.; Kvernadze, T.; Kakauridze, G.; Kilosanidze, B.
In this paper we present the innovative Polarization-Holographic Imaging Stokes Polarimeter which is developed based on a unique polarization-holographic diffraction element and allows one to determine full polarization of a light coming from a point or an extended space object in visual and near-infrared spectral ranges. Laboratory tests and first astronomical polarimetric observations show that the resulting errors are of the 10−4 order. As an example, the preliminary results of the polarimetric observations of some bright Algol-type variable stars and spicules are presented.
Keywords: Astronomy and Astrophysics